"Even If the Policy Changes, the Culture Remains the Same": A Mixed Methods Analysis of LGBT Service Members' Outness Patterns. Issue 3 (July 2021) - McNamara, Kathleen A.; Lucas, Carrie L.; Goldbach, Jeremy T.; Castro, Carl A.; Holloway, Ian W.
Despite repeal of the Don't Ask, Don't Tell policy in 2011 and the ban on open transgender service from 2016 to 2019, lesbian, gay, bisexual, and transgender (LGBT) service members may be reluctant to disclose their identities to fellow military personnel. This study used data collected through the Department of Defense–funded mixed methods research study conducted from 2016 to 2018. A sample of 248 active duty LGBT service members completed a survey, while a sample of 42 LGBT active duty service members participated in an in-depth interview. Regression analyses tested for differences in outness by demographic and military traits; a thematic analysis of qualitative data contextualizes these findings. Outness to fellow service members varied greatly by rank, military branch, education level, sexual orientation, gender identity, and marital status. The lowest outness was to chaplains (38%), while the highest outness was to LGBT unit friends (93%). Implications for military leadership and service providers are discussed.